2020
DOI: 10.1017/s0016756820000576
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircon provenance of north Gondwana Palaeozoic sandstones from Saudi Arabia

Abstract: We present the first comprehensive detrital zircon U–Pb age dataset from Palaeozoic sandstones of Saudi Arabia, which provides new insights into the erosion history of the East African Orogen and sediment recycling in northern Gondwana. Five main age populations are present in varying amounts in the zircon age spectra, with age peaks at ~625 Ma, ~775 Ma, ~980 Ma, ~1840 Ma and ~2480 Ma. Mainly igneous rocks of the Arabian–Nubian Shield are suggested to be the most prominent sources for the Ediacaran to middle T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 80 publications
4
12
0
Order By: Relevance
“…A more plausible source for 750-850 Ma U-Pb age zircons is the Paleozoic siliciclastic section of northern Saudi Arabia (Figure 1). Detrital zircons from the Saudi Paleozoic section in Al Jauf area show a significant age population at 750-850 Ma (Garzanti et al, 2013;Meinhold et al, 2020), as found here in the Hordos and Ein Gev Sands formations (Figure 7). This may suggest that parts of the Paleozoic sequence of northern Saudi Arabia, particularly its upper Devonian section, were recycled into the fluvial system that transported siliciclastic material onto the northern Miocene strata of Israel.…”
Section: Heavy Minerals Perspectivesupporting
confidence: 66%
See 3 more Smart Citations
“…A more plausible source for 750-850 Ma U-Pb age zircons is the Paleozoic siliciclastic section of northern Saudi Arabia (Figure 1). Detrital zircons from the Saudi Paleozoic section in Al Jauf area show a significant age population at 750-850 Ma (Garzanti et al, 2013;Meinhold et al, 2020), as found here in the Hordos and Ein Gev Sands formations (Figure 7). This may suggest that parts of the Paleozoic sequence of northern Saudi Arabia, particularly its upper Devonian section, were recycled into the fluvial system that transported siliciclastic material onto the northern Miocene strata of Israel.…”
Section: Heavy Minerals Perspectivesupporting
confidence: 66%
“…Kernel Density Estimation (KDE) plots for detrital zircon (teal/gray) and rutile (orange/tan) in the northern and southern Miocene sedimentary provinces (combined) and possible provenance units (data from Avigad et al., 2017; Garzanti et al., 2013; Kolodner et al., 2006, 2009; Meinhold et al., 2020), focused on the early Paleozoic – late Mesoproterozoic time interval (400–1,400 Ma). KDE bandwidth is 20 Ma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on ion-microprobe U-Pb analyses of detrital zircon grains from various Neoproterozoic to Cambrian sandstones of the Alborz and Zagros mountains and from the basement of the Central Iranian plateau, Horton et al (2008) proposed that a basal clastic succession representing the earliest sedimentary record in Iran displays a provenance age signature dominated by Pan-African (0.9-0.6 Ga) rocks, which are similar to detrital zircon age spectra for age-equivalent units of the west and south in Israel, Jordan, Egypt and Saudi Arabia in northern Gondwana (e.g. Avigad et al 2003Avigad et al , 2015Avigad et al , 2017Kolodner et al 2006;Meinhold et al 2021). Because of the lack of significant pre-600 Ma detrital zircon ages, these authors have therefore concluded that the main sources were likely located in Pan-African basement provinces of Arabia and Africa, particularly in the Arabian-Nubian shield, although the Iranian basement may have contributed some sediment.…”
Section: B2a Correlation Of Gondwanan Detrital Zircon Age Spectramentioning
confidence: 99%